A proposed information systems strategic plan of the University of the Philippines School of Library and Information Studies 2008-2013 - Simbol, Raffy, P.; Tinao, Maria Maura S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
The University of the Philippines School of Library and Information Studies is the premiere library school of the Philippines and Asia. It is the first library institution to capitalize on information technology embedding it to different Library and Information Science tracks. The school envisions to have high tech facilities to support the courses that it offers. To be able to obtain this vision, SLIS must have a plan on its acquisition, use and maintenance of its IT infrastructure.
An Information Systems Strategic Plan is a sound solution for the achievement of goals of the School. It is a process where the school's IT needs are realigned to the current technologies available in the market. Determining the needs of the school yields to students' skills and assessment of the IT infrastructure. The inputs of the Dean, Faculty and System administrator provide vital roles in crafting the said plan.
Survey questionnaires were deployed to SLIS students and faculty while interview questions were addressed to the Dean and Systems administrator. Students gave their views and supplied answers in the open ended questions. Assessment with the IT environment was done and skills were quantified using metrics and scale. Several issues were also raised by the systems administrator, such claims include: inadequate network bandwidth, few computer systems, etc. The Dean has a positive outlook towards the advancement of the School. These make up a good justification for the crafting of an Information Systems Strategic Plan.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman, School of Library and Information Studies -- Planning